2020
DOI: 10.1159/000511964
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Detection on Bronchoalveolar Lavage: An Italian Multicenter experience

Abstract: <b><i>Background:</i></b> Bronchoscopy with bronchoalveolar lavage (BAL) during the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) pandemic should be reserved to a limited number of clinical indications. The yield of BAL for the diagnosis of suspected or confirmed pulmonary SARS-CoV-2 infection is still unknown. <b><i>Objectives:</i></b> We aimed to evaluate the diagnostic ratio of BAL in detecting SARS-CoV-2 pulmonary infection in patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 20 publications
4
73
2
3
Order By: Relevance
“…Information obtained from the bronchoscopy were noted, as well as the main chest CT features. This paper differs from the previous one [6] for methodological evaluation of CT scans: in particular, each patient's CT scan was evaluated in consensus by two expert radiologists and for each case the likelihood of COVID-19 pneumonia was reported, based on STR/RSNA and CO-RADS standards [2,3]. The two readers acquired their COVID-19 experience participating in a previous study [4] where they reviewed in consensus 773 CTs for suspected SARS-CoV-2 infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information obtained from the bronchoscopy were noted, as well as the main chest CT features. This paper differs from the previous one [6] for methodological evaluation of CT scans: in particular, each patient's CT scan was evaluated in consensus by two expert radiologists and for each case the likelihood of COVID-19 pneumonia was reported, based on STR/RSNA and CO-RADS standards [2,3]. The two readers acquired their COVID-19 experience participating in a previous study [4] where they reviewed in consensus 773 CTs for suspected SARS-CoV-2 infection.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a retrospective single-center study approved by the institutional committee on human research (protocol number, CE 97/20). Patients included in the current study are part of a previously published study ( 6 ). We included all the consecutive patients from March 16 to May 19, 2020, who underwent a chest CT scan after two consecutive negative nasopharyngeal swabs and followed by bronchoscopy with BAL with RT-PCR testing for SARS-CoV-2 RNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Patrucco et al reported that of the 120 patients with 2 negative swabs, SARS-CoV-2 was isolated (27.5%) on BAL. (9)…”
Section: Discussionmentioning
confidence: 99%
“…Patrucco and colleagues ( 3 ) present a single-center retrospective study of the diagnostic performance of chest CT in patients suspected of having COVID-19 pneumonia, an imaging analysis of a subset of patients from a recently published study of 131 patients tested by using BAL for SARS-CoV-2 ( 7 ). They evaluated 46 patients who underwent a chest CT examination after two consecutive negative nasopharyngeal swab PCRs, using BAL an average of 1–2 days after the upper respiratory tract swabs as the reference standard ( 3 ).…”
mentioning
confidence: 99%